Treatment of Warts by Immunotherapy Using Purified Protein Derivative - Choudhary, Dilip; Piya, Silviya (Birat Journal of Health Sciences, 2018)
Introduction: Spontaneous clearance of warts has been reported with the development of cell mediated immunity. Various antigens and vaccines have been used for the non specific stimulation of cell mediated immunity and purified protein derivative (PPD) is one of them. Objective: To assess the effectiveness of intralesional PPD injection for the clearance of cutaneous warts. Methodology: This is an open labeled study and non-probability sampling method was used for enrolling the cases. Patients with cutaneous warts were injected with PPD intralesionally (2.5 TU) at an interval of 2 weeks for a total of five sessions and they were followed for 6 months after they received the last session therapy. Results: A total of 52 patients,29 males and 23 females, were enrolled in the study and among them 28 patients had verruca vulgaris,12 patients had verruca plantaris, 9 patients had periungual wart and 3 patients had verruca plana. Total clearance of warts was seen in 78.8%(41) of patients, however 21.2% (11) patient did not respond to the therapy. Most of the patients tolerated the therapy well and few of them had mild side effects like erythema, pain and oedema at the site of injection. Conclusion: Immunotherapy with intralesional injection of PPD is a safe and effective way to treat cutaneous warts with good response rate. BJHS 2018;3(2)6: 463-467.